Using lignin from local biorefineries for asphalts: LCA case study for the Netherlands. (1st April 2022) - Moretti, Christian; Hoefnagels, Ric; van Veen, Marco; Corona, Blanca; Obydenkova, Svetlana; Russell, Scott; Jongerius, Anna; Vural-Gürsel, Iris; Junginger, Martin
Abstract: The production of bio-based asphalt utilizing lignin from amongst others local biorefineries is currently under development in the Netherlands. In this study, life cycle assessment (LCA) methodology was applied to investigate the environmental implications of replacing conventional asphalts with lignin-based asphalts. Inventory data for lignin were collected from two Dutch biorefining industries (Avantium and Vertoro). Eleven impact categories were considered, along with a single-score environmental cost indicator. For the comparative assessment, both kraft lignin asphalts and conventional asphalts were used as benchmarks. The effect of a change of allocation method was discussed. Process steam, chemicals (mainly hydrochloric acid or methanol) and electricity were identified as the main environmental hotspots of the two biorefineries. Comparing on the basis of the same steam source, both biorefinery lignins showed lower climate change (up to 45% lower) and environmental cost (up to 60%) than kraft lignin. Top-layer asphalts using biorefinery lignins showed a 35–70% lower climate change impact than conventional asphalts. For base-layer asphalts, 25–50% reduction of climate change was calculated compared to conventional asphalts. On an environmental cost-weighted basis, besides climate change, other relevant environmental impacts are marine aquatic ecotoxicity, human toxicity, eutrophication and acidification. Using mass allocation instead of economic allocation showed that the environmental impact of lignin can increase, decrease or remain unchanged depending on the production system and co-products of lignin. Highlights: The environmental life cycle of bio-based asphalts is investigated. Lignin from local biorefineries was modelled based on primary data. Bio-based asphalts using lignin from local biorefineries showed climate change benefits. Methodological uncertainties related to multifunctionality and biogenic carbon modeling are broadly discussed.